Formulaic or not? The most important characteristics of formulaic sequences - Czarnecka, Małgorzata (Glottodidactica, 2010)
Formulaic sequences constitute a large protection of any discourse and, furthermore, they exist in so many forms that it is difficult to develop an adequate definition of this phenomenon. The term formulaic sequences encompasses verious types of world strings which appear to be stored and retrieved as holistic units from the memory. This article outlines some improtant aspects of formulaic sequences; it also shows the variety of definitions which appear in the research literature, and tries to find some specific criteria by means of which formulaic sequences could be identified in a discourse or a text.